Evaluation of Scatter Correction using a Single Isotope for Simultaneous Emission and Transmission Data - Yang, J.; Kuikka, J. T.; Vanninen, E.; Kauppinen, T.; Länsimies, E.; Patomäki, L. (Nuklearmedizin - NuclearMedicine, 1999)
Photon scatter is one of the most important factors degrading the quantitative accuracy of SPECT images. Many scatter correction methods have been proposed. The single isotope method was proposed by us. Aim: We evaluate the scatter correction method of improving the quality of images by acquiring emission and transmission data simultaneously with single isotope scan. Method: To evaluate the proposed scatter correction method, a contrast and linearity phantom was studied. Four female patients with fibromyalgia (FM) syndrome and four with chronic back pain (BP) were imaged. Grey-to-cerebellum (G/C) and grey-to-white matter (G/W) ratios were determined by one skilled operator for 12 regions of interest (ROIs) in each subject. Results: The linearity of activity response was improved after the scatter correction (r = 0.999). The y-intercept value of the regression line was 0.036 (p <0.0001) after scatter correction and the slope was 0.954. Pairwise correlation indicated the agreement between nonscatter corrected and scatter corrected images. Reconstructed slices before and after scatter correction demonstrate a good correlation in the quantitative accuracy of radionuclide concentration. G/C values have significant correlation coefficients between original and corrected data. Conclusion: The transaxial images of human brain studies show that the scatter correction using single isotope in simultaneous transmission and emission tomography provides a good scatter compensation. The contrasts were increased on all 12 ROIs. The scatter compensation enhanced details of physiological lesions.
Keywords: Attenuation correction; fan-beam collimator; scatter correction; single photon emission computed tomography; transmission computed tomography